2017
DOI: 10.1007/s13320-016-0389-6
|View full text |Cite
|
Sign up to set email alerts
|

Proposal for all-optical switchable and tunable ultrawideband monocycle generation utilizing SOA wavelength conversion and time delay

Abstract: An all-optical ultrawideband monocycle generator based on wavelength conversion in a semiconductor optical amplifier (SOA) and optical tunable delay in an optical delay line (ODL) is proposed and simulated. The system achieves optically switchable in pulse polarity and tunable in both the pulsewidth and radio frequency (RF) spectrum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…Moreover, in most optical UWB signal generation schemes, the derivatives of Gaussian pulse are normally regarded as a kind of reference waveform [6] . And this type of UWB signals are widely used in the optical fiber UWB system (UWB-over-Fiber) [7][8][9][10][11][12][13] .…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, in most optical UWB signal generation schemes, the derivatives of Gaussian pulse are normally regarded as a kind of reference waveform [6] . And this type of UWB signals are widely used in the optical fiber UWB system (UWB-over-Fiber) [7][8][9][10][11][12][13] .…”
Section: Resultsmentioning
confidence: 99%
“…In UWB over fiber system, the primary task is to generate optical UWB signal. Numerous studies on optical UWB signal generation in the optical field have been reported [7][8][9][10] . One of the most common way to generate optical UWB signal is to derive the initial signal pulses with appropriate pulse width under different orders.…”
Section: Introductionmentioning
confidence: 99%